The study of signaling pathways controlling neuronal apoptosis inhibitory protein (NAIP) expression and function - Coffill, Cynthia Rose (University of Ottawa (Canada), 2006)
Deletions in the gene for Neuronal Apoptosis Inhibitory Protein ( NAIP) have been suggested to exacerbate the severity of motor neuron loss in patients with Spinal Muscular Atrophy (SMA). NAIP is the founding mammalian member of the inhibitor of apoptosis (IAP) protein family that is characterized by highly conserved amino-terminal motifs called baculovirus IAP repeats (BIR). Previous in vitro and in vivo analyses with an adenovirus expressing NAIP but lacking exons 14 and 17 of the full-length cDNA (NAIPDeltaE14/17) displayed measurable cytoprotection against apoptosic-induced cell death. In the present study, cytoprotective effects were obtained with adeno-NAIPDeltaE14/17 alone in the human neuroblastoma SH-SYSY. Pretreatment of these cells with trophic factors failed to improve the cytoprotection mediated by NAIP. Similarly, the anti-apoptosic effect of NAIP was observed in HeLa cells transiently transfected with constructs expressing full-length NAIP and NAIPDeltaE14/17. To further investigate NAIP's cellular role, human HeLa and rat PC12 stable cell lines were developed by integrating a tetracycline-dependent transcription factor construct that was able to selectively regulate a second DNA construct containing full-length NAIP. Doxorubicin, etoposide and TNFalpha were used to test the cytoprotectiveness of NAIP. Surprisingly, cells overexpressing the full-length NAIP protein did not display increased survival, as determined by a WST-1 metabolism assay, suggesting that long-term exposure to an IAP may result in cellular compensatory mechanism. In an effort to delineate the signal transduction pathways that modulate the genes encoding marine Naip, the neuroblastoma cell line, neuro-2a was exposed to a number of signaling pathway specific inhibitors and activators. Cyclic AMP analogs, db-cAMP and 8-Br-cAMP both increased the Naip transcript, as did the plant isoflavone, genistein. Serum starvation was also found to increase Naip levels. We show that sodium butyrate (NaB), a broad-spectrum activator of many signaling pathways, increased the Naip mRNA levels of by 3-fold. By focusing on the NaB induction, it appears that Naip can be modulated by more than one signaling pathway as inhibition of JAK2 in the presence of NaB resulted in a significant and additive increase in the Naip transcript. In combination with various kinase inhibitors, the NaB-induced up-regulation was found not be dependent on the ERK, p38 or PKA pathways. A broad based kinase inhibitor, H-7 down-regulated Naip and also attenuated the NaB-induced up-regulation of Naip. Our data suggest that the Naip gene can be induced by NaB through the H-7 sensitive PKC or PKG but not PKA-pathways. To examine whether or not the third BIR domain of NAIP (NBIR3) inhibits caspase-9, recombinant GST-NBIR3 protein was overexpressed, purified, and successfully used to demonstrate inhibition of this initator caspase. Through binding analyses a Smac-based peptide, which has been shown to be an IAP antagonist, and NBIR3 were shown to interact with a KD of 52 nM and similar to the third BIR domain of XIAP (XBIR3). Interestingly, and in contrast to XBIR3, the processed Smac protein does not appear to interact with NBIR3 as association could not be detected during a pull-down study, suggesting that other interactions between the proteins are important. In a search for unique binding partners for NBIR3, a phage display library was panned for a binding consensus sequence. Following the identification of a number of human proteins containing this sequence, TRABID a candidate protein was chosen for testing. In the TNFalpha, signaling pathway, TRAF6 can interact with both TRABID and TAK1 while NAIP can bind TAK1 but it does not appear that TRABID and NBIR3 directly interact based on pull-down studies. Overall, through the examination of NAIP induction, signaling pathways that had not previously been associated with the up-regulation of an IAP were identified and characterized. In the exploration of anti-apoptosic activity, the third BIR domain of NAIP was shown to act in a similar mariner to the other IAPs containing three BIR motifs by inhibiting caspase-9 and interacting with a peptide based on the antagonist, Smac. These findings can potentially lead to therapeutic interventions in degenerative diseases with dysregulated apoptosis.
Keywords: Chemistry, Biochemistry.